Next-Level Solar Power Monitoring: Design and Implementation of an IoT-Based Solar Power Plant Monitoring System for Enhanced Efficiency and Performance - Engr. Shazia Feroz; Muhammad Ismail Saqib; Mudassar Rafique; Basit Ahmad; Shakeel Ahmed; Aneesa Zeb; Azhar Ali (Dialogue Social Science Review (DSSR), 2025)
The increasing demand for renewable energy sources has heightened the need for efficient and sustainable solar power generation. However, one of the critical challenges faced by solar power plants is the lack of real-time monitoring and performance analysis, which hinders the optimal operation and maintenance of these systems. This paper presents the design and implementation of an IoT-based solar power plant monitoring system aimed at enhancing efficiency and performance. The proposed system integrates a network of sensors, including temperature, voltage, current, and irradiance sensors, to collect real-time data from solar panels and other critical components of the plant. This data is transmitted to a centralized cloud-based platform, where advanced analytics and visualizations allow operators to monitor performance, detect faults, and optimize energy output. Additionally, the system offers predictive maintenance capabilities, reducing downtime and increasing the overall reliability of the plant. The results of a prototype implementation demonstrate significant improvements in system efficiency and performance, providing a scalable solution for modern solar power plants. This research highlights the potential of IoT technologies to revolutionize solar energy management and offers a foundation for further development in the field of smart, sustainable energy systems.